2018
DOI: 10.1016/j.jmii.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antibacterial activity of tigecycline against Vibrio vulnificus

Abstract: Our in vitro combination and animal studies indicate that tigecycline could be an option for the treatment of invasive V. vulnificus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In previous antimicrobial susceptibility studies using MIC testing, the susceptibility rate of E. anophelis to tigecycline ranged from 5.1% to 26.4% [7]. Although tigecycline is mainly considered to be a bacteriostatic antimicrobial agent [23], this new glycylcycline antibiotic exhibits bactericidal activity against some bacterial species, including Klebsiella pneumoniae, Acinetobacter baumannii, and Vibrio vulnificus [24][25][26]. However, our study revealed that tigecycline possessed only bacteriostatic activity against E. anophelis but no bactericidal effect, even at 4 × MIC.…”
Section: Discussionmentioning
confidence: 99%
“…In previous antimicrobial susceptibility studies using MIC testing, the susceptibility rate of E. anophelis to tigecycline ranged from 5.1% to 26.4% [7]. Although tigecycline is mainly considered to be a bacteriostatic antimicrobial agent [23], this new glycylcycline antibiotic exhibits bactericidal activity against some bacterial species, including Klebsiella pneumoniae, Acinetobacter baumannii, and Vibrio vulnificus [24][25][26]. However, our study revealed that tigecycline possessed only bacteriostatic activity against E. anophelis but no bactericidal effect, even at 4 × MIC.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In refractory cases, tigecycline has been reportedly used as an alternative salvage agent. 5,20,21 With global warming and pollution disrupting the marine microbiome, V. vulnificus incidence rates will continue to rise. For the clinician, obtaining a thorough epidemiological history will avoid unnecessary antibiotic delays.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro data from the present study demonstrated that the antibacterial effect of TGC alone was more distinctive than that of the DOX/CAZ combination (p = 0.028). Tang et al (Tang et al, 2016) previously reported that TGC monotherapy has a similar killing effect as the combination of minocycline and cefotaxime in experimental murine infection with V. vulnificus. In addition, a recent study (Lin et al, 2016) showed that patient who received TGC had a significantly favorable microbiological response and clinical outcomes, which is similar to one of the cases reported in the present study.…”
Section: Tablementioning
confidence: 91%